A nanoporous metal recuperated MnO2 anode for lithium ion batteries. Issue 37 (9th September 2015) - Guo, Xianwei; Han, Jiuhui; Zhang, Ling; Liu, Pan; Hirata, Akihiko; Chen, Luyang; Fujita, Takeshi; Chen, Mingwei
Abstract : A three-dimensional nanoporous gold/MnO2 composite has been explored as the anode for Li-ion batteries with high rate and cycling performances. Abstract : Lithium-ion batteries (LIBs) have been intensively studied to meet the increased demands for the high energy density of portable electronics and electric vehicles. The low specific capacity of the conventional graphite based anodes is one of the key factors that limit the capacity of LIBs. Transition metal oxides, such as NiO, MnO2 and Fe3 O4, are known to be promising anode materials that are expected to improve the specific capacities of LIBs for several times. However, the poor electrical conductivity of these oxides significantly restricts the lithium ion storage and charge/discharge rate. Here we report that dealloyed nanoporous metals can realize the intrinsic lithium storage performance of the oxides by forming oxide/metal composites. Without any organic binder, conductive additive and additional current collector, the hybrid electrodes can be directly used as anodes and show highly reversible specific capacity with high-rate capability and long cyclic stability.